PROX1 gene CC genotype as a major determinant of early onset of type 2 diabetes in slavic study participants from Action in Diabetes and Vascular Disease: Preterax and Diamicron MR Controlled Evaluation study. - Hamet, P; Haloui, M; Harvey, F; Marois-Blanchet, F; Sylvestre, M; Tahir, M; Simon, P; Kanzki, B; Raelson, J; Long, C; Chalmers, J; Woodward, M; et al. (Lippincott, Williams & Wilkins, 2017)
Background: The prevalence of diabetic nephropathy varies according to ethnicity. Environmental as well as genetic factors contribute to the heterogeneity in the presentation of diabetic nephropathy. Our objective was to evaluate this heterogeneity within the Caucasian population. Methods: The geo-ethnic origin of the 3409 genotyped Caucasian type 2 diabetes (T2D) patients of Action in Diabetes and Vascular Disease: Preterax and Diamicron MR Controlled Evaluation was determined using principal component analysis. Genome-wide association studies analyses of age of onset of T2D were performed for geo-ethnic groups separately and combined. Results: The first principal component separated the Caucasian study participants into Slavic and Celtic ethnic origins. Age of onset of diabetes was significantly lower in Slavic patients (P = 7.3 x 10-20), whereas the prevalence of hypertension (P = 4.9 x 10-31) and albuminuria (5.1 x 10-9) were significantly higher. Age of onset of T2D and albuminuria appear to have an important genetic component as the values of these traits were also different between Slavic and Celtic individuals living in the same countries. Common and geo-ethnic-specific loci were found to be associated to age of onset of diabetes. Among the latter, the PROX1/PROX1-AS1 genes (rs340841) had the highest impact. Single-nucleotide polymorphism rs340841 CC genotype was associated with a 4.4 year earlier onset of T2D in Slavic patients living or not in countries with predominant Slavic populations. Conclusion: These results reveal the presence of distinct genetic architectures between Caucasian ethnic groups that likely have clinical relevance, among them PROX1 gene is a strong candidate of early onset of diabetes with variations depending on ethnicity.